Outcome after laparoscopic and open resections of posterosuperior segments of the liver. Issue 6 (13th February 2017) - Scuderi, V.; Barkhatov, L.; Montalti, R.; Ratti, F.; Cipriani, F.; Pardo, F.; Tranchart, H.; Dagher, I.; Rotellar, F.; Abu Hilal, M.; Edwin, B.; Vivarelli, M.; et al.
Abstract: Background: Laparoscopic resection of posterosuperior (PS) segments of the liver is hindered by limited visualization and curvilinear resection planes. The aim of this study was to compare outcomes after open and laparoscopic liver resections of PS segments. Methods: Patients who underwent minor open liver resection (OLR) and laparoscopic liver resection (LLR) between 2006 and 2014 were identified from the institutional databases of seven tertiary referral European hepatobiliary surgical units. Propensity score‐matched analysis was used to match groups for known confounders. Perioperative outcomes including complications were assessed using the Dindo–Clavien classification, and the comprehensive complication index was calculated. Survival was analysed with the Kaplan–Meier method. Results: Some 170 patients underwent OLR and 148 had LLR. After propensity score‐matched analysis, 86 patients remained in both groups. Overall postoperative complication rates were significantly higher after OLR compared with LLR: 28 versus 14 per cent respectively ( P = 0·039). The mean(s.d.) comprehensive complication index was higher in the OLR group, although the difference was not statistically significant (26·7(16·6) versus 18·3(8·0) in the LLR group; P = 0·108). The mean(s.d.) duration of required analgesia and the median (range) duration of postoperative hospital stay were significantly shorter in the LLR group: 3·0(1·1) days versus 1·6(0·8) days in the OLR group ( P < 0·001), and 6 (3–44) versus 4 (1–11) days ( P < 0·001), respectively. The 3‐year recurrence‐free survival rates for patients with hepatocellular carcinoma (37 per cent for OLR versus 30 per cent for LLR; P = 0·534) and those with colorectal liver metastases (36 versus 36 per cent respectively; P = 0·440) were not significantly different between the groups. Conclusion: LLR of tumours in PS segments is feasible in selected patients. LLR is associated with fewer complications and does not compromise survival compared with OLR. Abstract : Laparoscopic equals open